Chlamydophila pneumoniae Infection and Its Role in Neurological Disorders - Contini, Carlo; Seraceni, Silva; Cultrera, Rosario; Castellazzi, Massimiliano; Granieri, Enrico; Fainardi, Enrico (Interdisciplinary Perspectives on Infectious Diseases, 2010)
Chlamydophila pneumoniae is an intracellular pathogen responsible for a number of different acute and chronic infections. The recent deepening of knowledge on the biology and the use of increasingly more sensitive andspecific molecular techniques has allowed demonstration of C. pneumoniae ina large number of persons suffering from different diseases including cardiovascular (atherosclerosis and stroke) and central nervous system (CNS) disorders. Despite this, many important issues remain unanswered with regard to the role that C. pneumoniae may play in initiating atheroma or in the progression of the disease. A growing body of evidence concerns the involvement of this pathogen in chronic neurological disorders and particularly in Alzheimer's disease (AD) and Multiple Sclerosis (MS). Monocytes may traffic C. pneumoniae across the blood-brain-barrier, shed the organism in theCNS and induce neuroinflammation. The demonstration of C. pneumoniae byhistopathological, molecular and culture techniques in the late-onset AD dementia has suggested a relationship between CNS infection with C. pneumoniae and the AD neuropathogenesis. In particular subsets of MS patients, C. pneumoniae could induce a chronic persistent brain infection acting as a cofactor in the development of the disease. The role of Chlamydia in the pathogenesis of mental or neurobehavioral disorders including schizophrenia and autism is uncertain and fragmentary and will require furtherconfirmation.